(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2017)
New Ru-nitrosyl complex with fluorenyl-terpyridine ligand was synthesized. The crystal structures of the complex and the ligand were studied by means of single crystal x-ray diffraction analysis. The practical value of the reference complex [RuII(py)4Cl(NO)](PF6)2·1/2H2O modification in order to improve its optical parameters and biological stability was shown. The alteration of the complex by substitution of monodentate pyridine rings with polydentate terpyridine ligand leads to the increased biological stability along with the conservation of high photochemical reactivity. Introduction of a bulky and electron-rich fluorenyl moiety increases the ability of the compound to participate in two-photon absorption (TPA) process, notably it increases the absorption cross-section of the complex. Application of TPA approach gives numerous advantages in biological studies and treatment, associated with photochemical influence on the biological system. The perspectives of further modification of ligand structure for improvement of its efficiency in two-photon absorption were studied by means of computational methods. The possibility of NO-release upon irradiation was proved for cis- and trans-[RuII(FT)Cl2(NO)](PF6) – complexes in one-photon absorption process by the irradiation of the compound in the presence of Griess reagent. The idea for evaluation of [Ru(NO)]-complex optical parameters was suggested on the base of computational methods. Considering these complexes as the systems with push-pull character, we can apply the simplified approach for TPA cross-section calculation. Two-level model of two-photon absorption gives a possibility to assess the efficiency of the transition in TPA and was applied in the current study.